Potential of renin-angiotensin system inhibition to improve metabolic bone disorders - Mahnaz Momenzadeh; Maryam Khosravian; Bhaskar VKS Lakkakula (Society of Diabetic Nephropathy Prevention, 2021)
Metabolic bone disorder is an abnormality of bones indicated by reduced bone mass and high risk of fractures. Several lines of evidence have demonstrated that the local bone tissue renin-angiotensin system (RAS) is directly involved in bone metabolism and influences the bone health. This review aimed to assess the role of RAS in bone metabolism and comparative effectiveness of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) in reducing the bone fractures. In summary, the clinical trials, in vivo studies, and functional - pharmacological experiments suggested that the RAS regulates bone marrow metabolism and influences the bone health. Hence, it warrants further investigation on the role of ACEIs and ARBs in reducing risk fractures.